Continuity and transformation in Nkole material culture: The Case of Marriage Pots - Namara, Grace; Kwesinga, Philip; Kioli, Felix Ngunzo; Emmanuel, Mutungi (Machakos University Press, 2024)
The study investigated continuity and transformation in Ankole material culture of western Uganda with a focusing on marriage pots. The main objective was to investigate how material culture using the case of marriage pots have been relevant to the Ankole community through forces of transformation. The investigation exercise involved qualitative and quantitative methods of data collection and analysis. Investigation commenced with administering questionnaires to 130 respondents. In way of obtaining a broader view of the transitional experience about marriage pots from a traditional to a contemporary paradigm, interviews were carried out in an exercise that involved 30 potters, 20 married couples and 20 elders. Findings indicated that there is a profound changed between the traditional and the contemporary Nkole marriage pots, ideally in terms that include; One, design (form), and finish as some young couples require them painted instead of smoking, secondly improved production in terms numbers because of the improved technology. Findings however highlighted threat factors to the continuity and transformation of Nkole marriage pots which included; decreased Nkole marriage Traditional inductions, and an influx of imported substitutes.
Keywords: Material culture; Continuity and transformation; Marriage pots